2021
DOI: 10.3390/s22010301
|View full text |Cite
|
Sign up to set email alerts
|

Towards Hybrid Energy-Efficient Power Management in Wireless Sensor Networks

Abstract: Wireless Sensor Networks (WSNs) are prone to highly constrained resources, as a result ensuring the proper functioning of the network is a requirement. Therefore, an effective WSN management system has to be integrated for the network efficiency. Our objective is to model, design, and propose a homogeneous WSN hybrid architecture. This work features a dedicated power utilization optimization strategy specifically for WSNs application. It is entitled Hybrid Energy-Efficient Power manager Scheduling (HEEPS). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Further, Roy et al [27] suggested a technique the enables privacy preservation with minimal verification latency during handover activity, based on experimental findings. Chéour et al [28] propose a power usage optimizer titled "Hybrid Energy-Efficient Power Manager Scheduling" (HEEPS) tailored to the needs of WSNs. The suggested power regulator is unique in that it combines many approaches, including time-out Dynamic Power Management, Dynamic Voltage and Frequency Scaling, and the Global Earliest Deadline First (GEDF) scheduler, to achieve greater scheduling efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, Roy et al [27] suggested a technique the enables privacy preservation with minimal verification latency during handover activity, based on experimental findings. Chéour et al [28] propose a power usage optimizer titled "Hybrid Energy-Efficient Power Manager Scheduling" (HEEPS) tailored to the needs of WSNs. The suggested power regulator is unique in that it combines many approaches, including time-out Dynamic Power Management, Dynamic Voltage and Frequency Scaling, and the Global Earliest Deadline First (GEDF) scheduler, to achieve greater scheduling efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In existing literature there are techniques that save energy optimizing various parameters of the WSN [28][29][30]. The current research targets to conserve energy through an optimized data storing approach to be used in WSN applications that require historical data related to monitor object activity.…”
Section: Limitations and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Termination criteria are as follows: The AWOA algorithm is eliminated since the best CHs are obtained for the satisfaction of a termination criterion. Based on the CH, the nearest SN nodes are formed to obtain a cluster [25].…”
Section: Searching For Prey (Exploration Phase)mentioning
confidence: 99%
“…Not with standing, a significant number of their applications are comparative, for example, condition observing or reconnaissance. Normally, the nodes comprise of a radio handset and a microcontroller controlled by a battery, and in addition some sort of smart dust for identifying light, warm, moistness, temperature, and so forth [1,2].…”
Section: Introductionmentioning
confidence: 99%